A COMPARATIVE STUDY OF CONTAMINATED RIPARIAN ZONE FOR ECO LANDSCAPE DEVELOPMENT STRATEGY - Amanda Rosetia (Vitruvian : Jurnal Arsitektur, Bangunan dan Lingkungan, 2021)
The transition between terrestrial and aquatic ecosystems has been known as Riparian Zone. The riparian zone is where generally water flows rarely stagnant, which river is an intermediate plateu. Conversely, rivers, stream or lakes water flows can be stagnant in common situation. Svejcar in his article stated that as transition, riparian zone tends to have characteristics of both upland and aquatics ecosystems. Water contamination brings the effect on reforming the environment degradation whether they are directly or indirectly discharged into water bodies without adequate treatment. Various notable water rehabilitation projects in leading countries led to their substantial economic returns for many aspects by the government-led initiatives. Nature-inclusive solution has been heavily concerned for the mega projects. In which ecological landscape design can provide the ecosystem services to balance the engineering driven restoration projects. To include, the best practice management requires extended understanding of the pattern in order to allow optimum evaluation of the process relationship. This research is conducted by an explanatory method where writer observe the relevant writings and theory to evaluate riparian areas with support on both primary and secondary data. A comparison table has been conducted to determine the most optimum approach has done by three different cities in two big countries. They are Siak River, Riau, Indonesia between Citarum River in Bandung and Yangtze River in China. This comparison will explain the elements observe among the three rivers and follow by the explanatory theory that has been conducted, a best practice management for landscape design to be evaluate.